PENGARUH MODEL THINK PAIR SHARE TERHADAP KETERAMPILAN MENULIS TEKS EKSPLANASI SISWA SMA - Rahmadani, Suci; Arief, Ermawati; Noveria, Ena (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACT This research is aimed to describe the influence cooperative model type think pair share concerning description essay writing skills of student class XI SMA Negeri 1 Padang Panjang. The research method of this study is experiment method with quasi experiment. The results of this study there was significant influence cooperative model type think pair share concerning description essay writing skills of student class XI SMA Negeri 1 Padang Panjang at significant level 95% with degrees of freedom (n1+n2)-2, namely ttable <tarithmetic (1,70<5,43). Ho was rejected and H1 was accepted because the results of the hypothesis test prove that value of ttable was smaller than tarithmetic. Kata kunci: pengaruh, kooperatif, think pair share, teks eksplanasi.